The Impact of Human Resource Management Practices on Organizational Commitment in the Ministry of Education: A Field Study in the Directorates of Education in the Governorates of Southern Jordan - Al - Zghailat, Alaa Abdul Hafez (Journal of Economic, Administrative and Legal Sciences, 2018)
The present study aimed at identifying the role of Human Resources Management Practices (Polarization and Recruitment, Performance Evaluation, Training and Development, Incentives and Rewards, and Empowerment) on improving the Organizational Commitment with its three emotional dimensions (Affective commitment, Continuance commitment, and Normative commitment). The study population included all Directorates of Education in the governorates of southern Jordan, 11 Directorates. The results of study: There isn’t inability in moderate level in human resources management practices, and there is also a high level of interest in these departments to achieve organizational commitment, There is a positive relationship between Human Resources Management Practices and Organizational Commitment with its three emotional dimensions. Some recommendations of the study: Human resources management practices need to be implemented within a strategic framework, taking into account the environmental conditions as well as the personal circumstances of employees to achieve and improve the level of organizational commitment in directorates of Education.